Risk of Herpes Zoster Among Psoriasis Patients Taking Biologics: A Network Meta-Analysis of Cohort Studies - Tang, Zhenwei; Shen, Minxue; Chen, Xiang (Frontiers in Medicine, 2021)
Background: Herpes zoster (HZ) has raised public concern. An increasing incidence of HZ can be seen in immunocompromise population, such as the psoriasis patients taking biologics. Real-world evidences are still needed to investigate the risks of HZ among patients receiving different biologics treatment. This study aims to summarize the findings from cohort studies. Methods: Herein, we performed a meta-analysis of cohort studies. We included studies referred to seven biologics (Adalimumab, Alefacept, Efalizumab, Etanercept, Infliximab, Rituximab, Ustekinumab) as well as methotrexate for psoriasis. We estimated summary relative risks (RRs) for HZ using pairwise and network meta-analysis. Results: Overall, 5 studies were included for analysis. A total of 32827.6 patient-years was observed. The result of the meta-analysis showed pooled HZ incidence rate of Adalimumab, which accounts for the most patient-years in our analysis, is 2.6 per 1000 patient-years. Our analysis based on several cohorts turns out an insignificant difference among the patients receiving Adalimumab, Alefacept, Efalizumab, Etanercept, Infliximab, Rituximab, Ustekinumab, and methotrexate. Conclusions: Based on this analysis, the type of mono-biologic treatment contributes little to the risk of HZ among psoriasis patients. Of note, the negative findings of our study do not mean the unnecessity of vaccination. More efforts must be taken to further determine HZ risk of different therapeutic strategies.